When biology takes over: TV formats like The Bachelor and The Bachelorette confirm evolutionary theories of partner selection - Lenhard, Alexandra; Minten, Marie-Pierre; Lenhard, Wolfgang (Frontiers in Psychology, 2023)
Introduction In this study, we investigated the impact of age on mate selection preferences in males and females, and explored how the formation and duration of committed relationships depend on the sex of the person making the selection. Methods To this end, we utilized data from the television dating shows The Bachelor and The Bachelorette. In these programs, either a single man (“bachelor”) or a woman (“bachelorette”) has the opportunity to select a potential long-term partner from a pool of candidates. Our analysis encompassed a total of n = 169 seasons from 23 different countries, beginning with the first airing in 2002. Results We found that the likelihood of the final couple continuing their relationship beyond the broadcast was higher in The Bachelorette than in The Bachelor, although the duration of these relationships was not significantly influenced by the type of show. On average, women were younger, both when selecting their partner and when being chosen. However, men exhibited a greater preference for larger age differences than women. Furthermore, the age of the chosen male partners significantly increased with the age of the “bachelorettes,” whereas “bachelors” consistently favored women around 25.5 years old, regardless of their own age. Discussion We discuss these findings within the context of parental investment theory and sexual strategies theory.